The effect of different molecular weight chitosan on the physical and mechanical properties of plasticized films - Mutasher, Sara Hikmet; Al-Lami, Hadi Salman (European Journal of Chemistry, 2022)
Packaging materials based on biodegradable polymers are a viable alternative to replacing conventional plastic packaging of fossil origin. The main two factors affecting functionality and performance are the molecular weight and the type of plasticizer used in these materials. The goal of this research was to modify unfractionated plasticized chitosan films to improve the physical and mechanical characteristics of the original unfractionated chitosan films. Chitosan extracted from local shrimp shells was zone-refined to produce five distinct chitosan fractions with molecular weights ranging from 1.089×105 to 5.605×105 g/mole. The unfractionated and fractionated chitosan films plasticized with 1:3 poly(vinyl alcohol) and 2:1 maleic acid were prepared by casting from their 2% acetic acid solutions. They were examined by FT-IR and were found to be comparable to the native chitosan spectrum, indicating that the primary backbone of the chitosan structure was unaltered. Therefore, the effects of molecular weight fractions and the type of plasticizer on the physical and mechanical properties were investigated. Examining the films’ surface topography by atomic force microscopy revealed that increasing the molecular weight of chitosan fractions from 2.702×105 to 5.605×105 g/mole affects the surface morphology of the chitosan: poly(vinyl alcohol) (1:3) film. This was accompanied by an increase in the surface roughness of the resulting film from 0.953 to 2.82, and for chitosan: maleic acid from 0.509 to 1.62. It was found that the tensile strength and Young’s modulus of the cast films decreased and the percent elongation at break of the plasticized fractionated chitosan films was increased, implying that less stiff films were obtained with fractionated chitosan. The outcome of this work suggests that the biodegradable fractionated chitosan blend film is a promising packaging material and that poly(vinyl alcohol) is the most suitable plasticizer for this formulation.